Evalution of thin films prepared from carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) entrapped with candida rugosa lipase for enhanced biocatalytic efficacy - Siti Aiyshah Binti Md Razali
Candida rugosa lipase (CRL) immobilized into the carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) thin films via the entrapment method was studied. Characterization of the thin films which was done using Scanning electron microscope (SEM) coupled with Electron dispersive X-ray (EDX) elemental analyzer, X-ray diffractometer (XRD) and Fourier transform infrared (FTIR) spectrometer showed that entrapment of the biocatalyst had occurred within the thin films. Characterization of the immobilized CRL within the polymeric thin films using SEM showed a mass of globular patterns which confirmed the existence of CRL on the surfaces of the supports. The analysis on the elemental compositions of all thin films showed that carbon (C), oxygen (O) and sodium (Na) were major elements in the thin films, while thin films containing CRL showed the existence of potassium (K) in addition to the major elements mentioned above. In the analysis using XRD, all of thin films exhibited almost similar d-spacings of between 4.14418 to 4.65414 Å and 2θ values of between 19.054o to 21.424o. Similar peaks were also detected for all thin films in the analysis using FTIR spectrometer. The newly prepared biocatalyst thin films were then tested for their abilities in catalyzing the esterification of butyl oleate, in reactions which consisted of butanol and oleic acid. Thin films of CMC-CRL, PVA-CRL and PVA:CMC-CRL, showed 2-3 folds higher yields of butyl oleate compared to 9% yield of ester produced without CRL. The effect of storage stability at different temperatures (-20oC, 0oC, 4oC and room temperature) was also evaluated where the highest percent of conversion (28.9%) was obtained using PVA-CRL at storage temperature of -20oC. In the operational stability study, it was observed that the CMC-CRL, PVA-CRL and PVA:CMC-CRL were capable of retaining 50% of their catalytic activities even after 10 cycles of repeated uses. A kinetic study was also done to evaluate the efficacy of the free CRL and immobilized CRL. In the study, all immobilized CRL generally showed higher reaction rates than the free CRL. There were 2 types of conditions whereas at constant concentration of butanol and varying viii concentration of oleic acid and vice versa. PVA:CMC-CRL thin film showed the highest reaction rate compared to the free CRL . The immobilised lipases such as CMC-CRL, PVA-CRL and PVA:CMC –CRL have also showed considerably higher Vmax(Ol) compared to the native one in reactions of different concentration of oleic acid. The study of kinetics findings of one substrate (CMC-CRL, PVA-CRL and PVA:CMC-CRL) and two substrates (native-CRL) competitive were clearly explained by Bi Bi Ping Pong Model mechanism. These results indicated that the polymeric materials used for the entrapment of lipase in this study are potential supports for maintaining stability and activity of CRL for application in organic syntheses.